THE CORRELATION BETWEEN SELF CONFIDENCE AND STUDENTS’ SPEAKING PERFORMANCE AT SMP NEGERI 1 TOMBARIRI - Silalahi, Grachia Agustine; Hampp, Paula; Kamagi, Sarah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study aims to evaluate whether there is a correlation between the level of self-confidence and students’ speaking performance. The study was carried out at SMP Negeri 1 Tombariri, with research subjects totaling 28 students in the eighth grade. The data collection method used quantitative method, involving the use of self-confidence questionnaires and speaking tests, which are then analyzed through manual correlation analysis methods using the Pearson Product-Moment formula. Based on the results of the Pearson Product Moment Correlation Coefficient, the correlation between the level of self-confidence and student speaking performance (rxy) is 0.832. These findings indicate that H1 is accepted while H0 is rejected, indicating a significant correlation between students’ level of self-confidence and their speaking abilities at SMP Negeri 1 Tombariri, especially in English subjects. In conclusion, there is a significant correlation between students’ level of self-confidence and their speaking performance. Suggestion of this research is teachers should have better sensitivity in recognizing students’ personalities in order to manage them well when training students who are less active in the classroom. When carrying out the speaking learning process, teachers must ensure that the atmosphere remains relaxed and full of humor, and to give students more opportunities to practice speaking and participate in oral activities without feeling worried